Implementasi Model Pembelajaran Inklusi bagi Peserta Didik Learning Disability di Sekolah Dasar Negeri Kota Mataram - I Ketut Widiada; Sudirman Sudirman; Darmiany Darmiany; Ide Kade Gunayasa; Muhammad Syazali (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
The aims of research are to; 1) describe the types of learning difficulties of SNS, 2) Identifying the learning model applied by the classroom teacher to students with learning disabilities, and 3) describe the development of students' learning behavior academically and socially towards students with learning disabilities. The research was conducted on inclusive students in elementary schools throughout the city of Mataram. This research method uses qualitative and quantitatif research methods. The research subject consist of 67 inculsive students. Data were collected through direct observation, interviews and documentation. Data analysis was carried out descriptively to measure proportions and averages. The result of study show that; 1) types of learning difficulties experienced by students in inclusive learning at Public Elementary Schools in Mataram include cognitive learning difficulties such as perceptual disorders, cognitive thinking disorders, symbolization, language reasoning; solving academic learning problems which include difficulties in learning to read (dyslexia), difficulties in learning to write (dysgraphia) and difficulties in learning to count; and emotional and social behavior disorders, 2) the inclusive learning model used is a regular learning model to change students' views about children who have learning problems and do not experience learning problems so that class conditions are cooperative, and 3) the application of inclusive learning improves the development of the learning abilities of SNS between odd and even semesters.